Costs of implantation and management of Gladiolus in the organic notillage system in Laranjeiras do Sul/PR (Research, Society and Development, 2022)
The knowledge of economic aspects is of paramount importance for the implementation of a project, thus, in the southern region of Brazil, commercial floriculture is recent, but the activity has been growing and obtaining expressive data during the last five years. As such, the commercial cultivation of gladiolus (Gladiolus x grandiflorus Hort.), in the form of organic no-tillage, presents scarce studies and technical data, and there is still a lack of information, such as implementation costs and the main technical coefficients, making the analysis more difficult. need the possibility of deployment. The objective of this research was to determine the main technical coefficients, implantation and management costs of one hectare of gladioli in an organic no-till system in Laranjeiras do Sul/PR. The study was conducted in the period 2020/21 where there were consultations in the literature on all aspects of the gladiolus production chain, such as technical data, cultural practices and production, among others. Information was also collected from researchers, in addition to the installation of an experiment in order to validate the study carried out. The total costs of implantation and management of one hectare of gladiolus reached R$ 235,895,529 whose most significant components in the composition of the costs were the expenses with inputs, especially the acquisition of organic fertilizers and bulbs. The mechanized and manual operations, on the other hand, resulted in values with a low proportion of the total cost, with “other inputs” being the smallest share. Thus, it is concluded that the determination of implementation and management costs is of great importance, as it can be attractive to investors and farmers.